Cross Infection Control Practices in Dental Clinics: A Patient Perspective - Naeem Asim, Nashida Ahmed, Muhammad Hassan Khoso, Reema Aslam, Zaka Un Nisa, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the knowledge, attitudes and practices of cross-infection control measures at dental clinics in Islamabad, Pakistan. Study Design: A cross-sectional study was designated to assess the knowledge, attitudes, and practices of cross-infection control measures. Place and Duration: The study was carried out in dental clinics in Islamabad for six months. Methodology: A pretested questionnaire comprised of thirty questions was administered to respondents. The sample size comprises patients who visited the dental hospitals of Islamabad and Rawalpindi. The data were analyzed using SPSS statistical software. Results: Most of the respondents (69.8%) showed poor knowledge. However, among respondents 85.6%presented a positive attitude towards infection control measures. Concerning self-reported practices, approximately 16% and 17% of patients ask the dentist to wear gloves and a face mask. Only 12% ask the dentist whether instruments are sterilized or not. A significant difference was seen between the education of patients and knowledge towards cross-infection control measures. Among respondents with a high level of education, 87.7% showed good knowledge, whereas the medium (58.6%) and low level of education (9.8%) showed good knowledge towards infection control measures, respectively. Conclusion: In conclusion, our results showed poor knowledge and practice regarding cross-infection control measures; however, most respondents demonstrated a positive attitude. Keywords: Infection control, Dental patient, Emerging disease, Risk, Knowledge, Attitude